2013
DOI: 10.1371/journal.pone.0080957
|View full text |Cite
|
Sign up to set email alerts
|

Looking Like a Leader–Facial Shape Predicts Perceived Height and Leadership Ability

Abstract: Judgments of leadership ability from face images predict the outcomes of actual political elections and are correlated with leadership success in the corporate world. The specific facial cues that people use to judge leadership remain unclear, however. Physical height is also associated with political and organizational success, raising the possibility that facial cues of height contribute to leadership perceptions. Consequently, we assessed whether cues to height exist in the face and, if so, whether they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 73 publications
6
40
1
Order By: Relevance
“…Other recent work has reported that perceived 'tallness' in the face and facial adiposity (i.e. fatness) are associated with judgements of leadership ability (Re, Dzhelyova, Holzleitner, Tigue, Feinberg & Perrett, 2012;Re, Hunter, Coetzee, Tiddeman, Xiao, DeBruine, Jones & Perrett, 2013;Re & Perrett, 2014). Collectively, these findings suggest that physical appearance plays a role in the workplace and particularly in our views of others' leadership abilities.…”
Section: Appearance and Social Interactionsmentioning
confidence: 59%
“…Other recent work has reported that perceived 'tallness' in the face and facial adiposity (i.e. fatness) are associated with judgements of leadership ability (Re, Dzhelyova, Holzleitner, Tigue, Feinberg & Perrett, 2012;Re, Hunter, Coetzee, Tiddeman, Xiao, DeBruine, Jones & Perrett, 2013;Re & Perrett, 2014). Collectively, these findings suggest that physical appearance plays a role in the workplace and particularly in our views of others' leadership abilities.…”
Section: Appearance and Social Interactionsmentioning
confidence: 59%
“…Regarding the above30 ° condition, which is equivalent to a taller person looking down on a smaller person, recent research revealed that taller persons are associated with greater leadership skills (Re et al, 2012, 2013). From this point of view, you may expect that smaller persons indeed rely on the helpfulness of the respective leader instead of being more helpful themselves.…”
Section: Discussionmentioning
confidence: 99%
“…We created five composite images (each one created by averaging a random selection of three original male faces together) and masked them to occlude clothes with a black oval around the head. We then created "prototypes" to use for 8 transforming the composites in perceived height, masculinity, and age (see Re et al, 2013b for details).…”
Section: Stimulimentioning
confidence: 99%
“…Facial cues to height, which correlate with actual height (Burton & Rule, 2013;Re et al, 2013b), have also been found to influence perceptions of dominance (Windhager, Schaefer, & Fink, 2011). One study found that facial cues associated with tall physical stature increase perceived dominance (Re et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%